Microbiological characteristics of pork carcasses and vacuum packaged blade steaks during storage at 0±1°C - Najar-Villarreal, Francisco (Kansas State University, 2018)
To evaluate the effect of extended post-harvest hanging time on pork sides and the microbial shelf-life of fabricated steaks, aerobic plate count (APC), Enterobacteriaceae (EB), yeast and mold populations, pH, and moisture content of pork sides hung for 21 days at 0±1°C was determined. After hanging, blade steaks fabricated from these sides were vacuum packaged, stored up to 35 days at 0±1°C, and evaluated for APC, EB, yeast and mold populations, and pH. Carcass cooler temperature and percent relative humidity, measured every hour during storage, averaged 0±1°C and 87.3% (66-100%), respectively. Pork carcass surface moisture content declined (P ≤ 0.05) from 65.1% on day 1 to 50.5% on day 21. The carcass pH was similar (P ≥ 0.05) at 5.88 on days 1, 7, and 14; however, by day 21 the pH declined (P ≤ 0.05) to 5.72. The flank, shoulder, and jowl were sampled on pork carcasses. There was no day effect for carcass APC; however, there was a location effect. The jowl had the highest (P ≤ 0.05) APC with 1.21 log CFU/cm². There was no carcass location or day effect for EB or mold populations, but there was a carcass location and day effect for yeast populations. The detection limit (DL) for EB and yeast and mold populations on pork carcass samples (n = 240) was 0.06 and 0.41 log CFU/cm² for the shoulder and flank, and jowl, respectively. For EB and mold populations, 98.8 and 97.9% of carcass samples, respectively, were below the DL. For yeast populations, 37.5, 45.0, and 63.8% were above the DL for flank, shoulder, and jowl, respectively. On days 1, 7, 14, and 21, 60.0, 55.0, 53.3 and 26.6% were above the DL, respectively, for carcass yeast populations; however, none were greater than 2.83 log CFU/cm². The pH of pork steaks was 5.69-5.89. There was a day effect for APC on pork steaks. The initial APC of steaks was 1.61 log CFU/g, increasing (P ≤ 0.05) to 5.06 log CFU/g on day 35. There was a day effect for EB and mold populations; but not for yeast populations. The DL for EB and yeast and mold populations on pork steaks (n = 102) was 0.70 log CFU/g. On days 0, 7, 14, 21, 28, and 35, the percent of EB populations above the DL on pork steaks were 0.0, 0.0, 23.5, 41.2, 94.1, 41.2%, respectively, however, none of the steak samples exceeded 4.40 log CFU/g. For mold populations, 100.0% of steaks were below the DL on days 0, 7, and 14. On days 21, 28, and 35, 18, 24, and 12%, respectively, were above the DL. None of the steak samples exceeded 2.68 log CFU/g for mold populations. For yeast populations, 56.8% of pork steaks samples were above the DL, but none were greater than 3.69 log CFU/g. These results indicate that pork carcasses and vacuum packaged shoulder blade steaks fabricated from these carcasses have acceptable quality for 21 and 35 days, respectively, when stored at 0±1°C after harvest.
Keywords: blade steaks; microbial; pork carcass; storage